Crimson Lake - Fox, Candice (Thorndike, Maine : Center Point Large Print, 2018)
"A contemporary crime novel set in Queensland, Australia, finds Sydney detective Ted Conkaffey accused but not convicted of a brutal abduction. Maintaining his innocence, he agrees to help Amanda Pharrell, a convicted murderer turned private investigator, with a case full of deception and obsession"--
Keywords: Police -- Fiction -- Australia; Missing persons -- Fiction -- Investigation; Women private investigators -- Fiction; Large type books; Suspense fiction; Mystery fiction